THE ROLE OF INNOVATIVE PEDAGOGICAL CONSULTING IN THE ADAPTATION OF TECHNICAL UNIVERSITY STUDENTS (American Journal of Technology and Applied Sciences, 2023)
The article argues that a university student must find and choose ways and means to achieve a particular educational goal, while the teacher must create conditions for this. The article also deals with modern issues of higher education - the system of dual education in accordance with the requirements of the new State Educational Standards of the Republic of Uzbekistan.